2021
DOI: 10.3389/fnins.2021.755554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Hypoxia on Nervous System Development and Related Diseases

Abstract: The fetal origins of adult disease (FOAD) hypothesis, which was proposed by David Barker in the United Kingdom in the late 1980s, posited that adult chronic diseases originated from various adverse stimuli in early fetal development. FOAD is associated with a wide range of adult chronic diseases, including cardiovascular disease, cancer, type 2 diabetes and neurological disorders such as schizophrenia, depression, anxiety, and autism. Intrauterine hypoxia/prenatal hypoxia is one of the most common complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 122 publications
0
19
0
3
Order By: Relevance
“…In recent years, animal models of prenatal hypoxia have been widely used to understand the molecular mechanisms of adverse outcomes in offspring. Prenatal hypoxia affects fetal growth and elicits many disturbances after birth including the development of the central nervous system and cardiovascular regulatory system ( Peyronnet et al, 2000 ; Wang et al, 2021 ; Sutovska et al, 2022 ). Decreased oxygen supply and peripheral blood flow by gestational IH to the fetal organs such as the heart and brain have critical impacts on physiological functions of these organs ( Baschat et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, animal models of prenatal hypoxia have been widely used to understand the molecular mechanisms of adverse outcomes in offspring. Prenatal hypoxia affects fetal growth and elicits many disturbances after birth including the development of the central nervous system and cardiovascular regulatory system ( Peyronnet et al, 2000 ; Wang et al, 2021 ; Sutovska et al, 2022 ). Decreased oxygen supply and peripheral blood flow by gestational IH to the fetal organs such as the heart and brain have critical impacts on physiological functions of these organs ( Baschat et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Vázquez-Borsetti et al (2016) reported that a 20-min hypoxia-ischemia insult on perinatal rats led to social deficits and loss of neurons. However, hypoxia studies on prenatal and perinatal rodents often apply artery ligation to induce hypoxia-ischemia exposure ( Wang et al, 2021a ), which is much harsher than the hypoxia treatment in our study. Driscoll et al (2018) showed that 10% oxygen applied on pregnant Sprague-Dawley rats transiently for 3, 5, or 7 min combined with ligation of the infra-renal abdominal aorta and uterine arteries caused social deficits and inflammation in postcesarean pups at postnatal day 30.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been associated with other psychiatric disorders including schizophrenia and other non‐affective psychoses (Zornberg et al, 2000), but the exact mechanisms underlying this phenomenon are not clear. Altered epigenetic programming, endocrine axis dysfunction, and oxidative damage are hypothesized to be underlying mechanisms linking prenatal hypoxia with abnormal brain development and plasticity (reviewed in Wang et al, 2021). Thus, we cannot exclude that the link between low Apgar and offspring AN is hypoxia.…”
Section: Discussionmentioning
confidence: 99%